2018
DOI: 10.1159/000488904
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Cranial Ultrasound Abnormalities in Intrauterine Growth-Restricted Fetuses Born between 28 and 34 Weeks of Gestation: A Prospective Cohort Study

Abstract: Background: Doppler parameters have been commonly used for the prediction of neonatal outcomes. However, controversies exist with regard to the value of Doppler parameters in predicting the risk of neurological outcomes among neonates. Objective: This prospective cohort study attempted to assess the value of Doppler parameters in predict ing cranial ultrasound abnormalities (CUAs) in intrauterine growth restriction (IUGR) among fetuses at 28–34 weeks of gestation. Methods: This was a prospective cohort study o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 40 publications
(48 reference statements)
0
3
0
Order By: Relevance
“…CURs ≤ 1 are an important marker of fetal compromise and have been linked to adverse perinatal outcomes with strongest association in low birthweight babies [ 53 ]. Khazardoost also found that absent or reversed end-diastolic velocity in the UA and DV was associated with an increased rate of CUAs [ 54 ]. Although it is not possible to fully ascertain the benefit of cranial ultrasonography screening upon all growth-restricted infants, risk stratification may be a useful tool in the development of screening guidelines.…”
Section: Discussionmentioning
confidence: 99%
“…CURs ≤ 1 are an important marker of fetal compromise and have been linked to adverse perinatal outcomes with strongest association in low birthweight babies [ 53 ]. Khazardoost also found that absent or reversed end-diastolic velocity in the UA and DV was associated with an increased rate of CUAs [ 54 ]. Although it is not possible to fully ascertain the benefit of cranial ultrasonography screening upon all growth-restricted infants, risk stratification may be a useful tool in the development of screening guidelines.…”
Section: Discussionmentioning
confidence: 99%
“…The post-mortem studies revealed a decreased neuronal cortex density [ 22 ]. The disturbed neuronal migration and proliferation, observed in the hippocampus and in the septo-hippocampal circuit in FGR, are supposed to be responsible for learning and memory dysfunction [ 9 , 23 , 24 , 25 ]. Moreover, the impaired neuronal connectivity and myelination were described in animal models of placental insufficiency [ 23 , 26 ], and in human prematurely born FGR infants [ 9 , 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…The disturbed neuronal migration and proliferation, observed in the hippocampus and in the septo-hippocampal circuit in FGR, are supposed to be responsible for learning and memory dysfunction [ 9 , 23 , 24 , 25 ]. Moreover, the impaired neuronal connectivity and myelination were described in animal models of placental insufficiency [ 23 , 26 ], and in human prematurely born FGR infants [ 9 , 27 , 28 ]. Ramenghi et al noticed a significant reduction in the myelination in neonates with FGR and BS during pregnancy, as compared to neonates with FGR and normal middle cerebral artery flows [ 29 ].…”
Section: Introductionmentioning
confidence: 99%